City of beasts : How animals shaped Georgian London - Almeroth-Williams, Thomas (Book collections on Project MUSE., 2019)
This book explores the role of animals - horses, cattle, sheep, pigs and dogs - in shaping Georgian London. Moving away from the philosophical, fictional and humanitarian sources used by previous animal studies, it focuses on evidence of tangible, dung-bespattered interactions between real people and animals, drawn from legal, parish, commercial, newspaper and private records. This approach opens up new perspectives on unfamiliar or misunderstood metropolitan spaces, activities, social types, relationships and cultural developments. Ultimately, the book challenges traditional assumptions about the industrial, agricultural and consumer revolutions, as well as key aspects of the city's culture, social relations and physical development. It will be stimulating reading for students and professional scholars of urban, social, economic, agricultural, industrial, architectural and environmental history.